2011
DOI: 10.1073/pnas.1110817108
|View full text |Cite
|
Sign up to set email alerts
|

Direct binding of triglyceride to fat storage-inducing transmembrane proteins 1 and 2 is important for lipid droplet formation

Abstract: The process of lipid droplet (LD) formation is an evolutionarily conserved process among all eukaryotes and plays an important role in both cellular physiology and disease. Recently, fat storageinducing transmembrane proteins 1 and 2 (FIT1/FITM1 and FIT2/ FITM2) were discovered as an evolutionarily conserved family of proteins involved in fat storage. In mammals, FIT1 is expressed primarily in skeletal muscle and FIT2 is expressed primarily in adipose, raising the possibility that FIT1 and FIT2 have unique fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(162 citation statements)
references
References 28 publications
6
153
0
3
Order By: Relevance
“…The relative contribution of these two processes to lipid droplet growth is unknown, but there are instances where lipid transfer predominates ( 41,42,47 ). Multiple proteins appear to be involved in the recruitment of TG into lipid droplets in adipocytes, such as fat storage-inducing transmembrane 2 and fat specifi c protein 27 ( 49,50 ). We propose in CETP-expressing species that CETP also participates in this process, and our previous studies in CETP-defi cient cells support this hypothesis ( 14 ).…”
Section: Note Added In Proofsupporting
confidence: 71%
“…The relative contribution of these two processes to lipid droplet growth is unknown, but there are instances where lipid transfer predominates ( 41,42,47 ). Multiple proteins appear to be involved in the recruitment of TG into lipid droplets in adipocytes, such as fat storage-inducing transmembrane 2 and fat specifi c protein 27 ( 49,50 ). We propose in CETP-expressing species that CETP also participates in this process, and our previous studies in CETP-defi cient cells support this hypothesis ( 14 ).…”
Section: Note Added In Proofsupporting
confidence: 71%
“…It is interesting to note, however, that lipid droplets have recently been shown to bud into the ER lumen in cells lacking the fatstorage-inducing transmembrane (FIT) proteins (Choudhary et al, 2015). FIT proteins constitute an evolutionary conserved class of ER proteins that bind triacylglycerol in vitro and they are important for neutral lipid storage in vivo (Gross et al, 2011;Kadereit et al, 2008). Deficiency of FIT2 in the adipose tissue of mice results in progressive lipodystrophy of white adipose depots and metabolic dysfunction (Miranda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that FITs bind triacylglycerides (TAGs) and diacylglycerol, a precursor of TAGs 23 and thus the FITs may play a role in lipid metabolism that somehow affects LD production. Indeed one of the 2 FIT proteins in yeast has been genetically implicated in lipid metabolism but its role is not known.…”
mentioning
confidence: 99%